Effect of natural extreme events and human induced changes on the fish assemblage of a temperate estuarine system - Nyitrai, Daniel (2015)
Tese de doutoramento em Biociências, na especialidade de Ecologia Marinha, apresentada à Faculdade de Ciências e Tecnologia da Universidade de Coimbra